THE RELATIONSHIP BETWEEN LOGISTICS PLANNING AND LOGISTICS PROCUREMENT FUNCTIONS WITH THE AVAILABILITY OF MEDICAL DEVICES IN COMMUNITY HEALTH CENTERS IN KOLAKA DISTRICT: LOGISTICS PLANNING AND LOGISTICS PROCUREMENT - Dwi Ayu Hartati; Tasnim Tasnim; Sunarsih Sunarsih (STIKes Mandala Waluya Kendari, 2023)
Backgrounds: Health equipment is one aspect that supports the implementation of disease prevention (preventive) and disease healing (curative) efforts. The unavailability of medical equipment will affect the quality of services provided to patients. Based on data from the Medical Equipment Facilities and Infrastructure Application, none of the 14 (Fourteen) Community Health Centers in Kolaka Regency have medical devices that are fulfilled according to the Minister of Health. The purpose of this study is to analyze the relationship between Logistics Planning and Logistics Procurement Functions with the Availability of Medical Devices at Community Health Centers in Kolaka Regency Methods: This research is a quantitative study using the Cross-Sectional Study approach, the population in this study were 42 (forty-two) people and the sample in this study were 13 (thirteen) Community Health Centers. The data analysis used is descriptive and inferential analysis and logistic regression analysis Results: The results showed that the planning variable had a P Value = 0.583 <0.05, then procurement had a P Value = 0.513 <0.05, which means that the variables mentioned are related to the availability of medical devices and there is a simultaneous significant effect between management functions logistics on the availability of medical devices in Kolaka District. Conclusion: It is very necessary to have training or technical guidance on operating medical devices so that officers can operate and be able to maintain these medical devices.